Current trends and practices in the use of imprisonment. (10th January 2018) - Coyle, Andrew; Heard, Catherine; Fair, Helen
Abstract: This article charts the rapid rise in the use of imprisonment in recent decades before considering some of the most pressing issues of concern in the use of imprisonment today. First among these is prison overcrowding, which continues to blight the record of many countries in their treatment of prisoners. To illustrate the potentially dire consequences of overcrowding – a problem common to many other countries and regions – an account is given of a recent visit to a prison in El Salvador. The article then provides an overview of the relevant regional and international standards on the treatment of prisoners, referring also to the role of judicial bodies in ensuring implementation.